Pengaruh Thermal Shock dan Komposisi Grafit, Kaolin (Clay) terhadap Struktur Makro dan Ketahanan Impact Kowi Berbahan Dasar Limbah Evaporation Boats - Nurrohmah, Sinta Indiarti; Rusiyanto, Rusiyanto; Widodo, Rahmat Doni; Sumbodo, Wirawan (Jurnal Rekayasa Mesin, 2020)
The purpose of this study was to determine the effect of thermal shock and composition of graphite, kaolin (clay) on the macrostructure and impact resistance of crucible based on the waste of evaporation boats. The variation applied was composition waste of evaporation boats, graphite and kaolin 50%:25%:25%; 40%:30%:30%; 70%:15%:15%. Then the thermal shock standard temperature variation is ∆T = 100°C - 500°C. Specimens formed according to the ASTM D256 size (63.5x12.7x12.7) mm with compaction load 80 kg/cm2. Continuing the sintering process at a temperature of 1150°C holding time of 2 hours. Tests include XRD test for the waste of evaporation boats, thermal shock test, impact test and macro photo. The results showed that the highest average impact resistance is 0.01772659 Joule/mm2 with the composition of 50%: 25%: 25% without thermal shock. The lowest average resistance impact is 0.00637474 Joule/mm2 with the composition of 70%: 15%: 15% and 500°C thermal shock temperature. Based on the data, the higher treatment of temperature in thermal shock makes the lower impact resistance of the specimen.